Antecedents to performance ,measurement under results-based management: the case of local government agencies in East Java, Indonesia - Nurkholis, Nurkholis; Mohamad, Muslim Har Sani; Ismail, Suhaiza (2010)
This study examines factors affecting performance measurement (PM) utilization in local governments and its impact on accountability.Data for this study were collected from a self administered survey to program managers of local government agencies in East Java, Indonesia. Results from a structural equation model using Partial Least Square regression indicate that regulatory factors significantly affect utilization of performance measurement at the adoption stage. The relations of regulations, political supports and availability of resources with performance measurement implementation are mediated by goal orientation and management commitment which are the essential elements of results-based management. Utilization of performance measurement is shown to result in better accountability.